[RETRACTED] Location–Allocation Model Applied to Urban Public Services: Spatial Analysis of Fire Stations in Mysore Urban Area Karnataka, India - Javaid Ahmad Tali; Divya S; Asima Nusrath (Indonesian Journal of Geography, 2020)
This article was retracted due to the following reasons. Retraction note here: https://jurnal.ugm.ac.id/ijg/article/view/62031/pdf RETRACTION TO : Javaid Ahmad Tali, Divya S, Asima Nusrath (2020). Location–Allocation Model Applied to Urban Public Services: Spatial Analysis of Fire Stations in Mysore Urban Area Karnataka, India. Indonesian Journal of Geography, 52(2). 201-207 (doi. 10.22146/ijg.25365). This article has been retracted by Publisher based on the following reason:Double publish in Transactions of the Institute by Indian Geographers, 2019, 41(1), pp. 1-12 Based on clarification via email, Authors of the above paper have admitted their double publish to the previously published paper by Transactions of the Institute of Indian Geographers, 2019, 41(1), pp. 1-12We apologies are offered to readers of the journal that this was not detected during the submission process.